1998
DOI: 10.1016/s0022-2275(20)33294-6
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of pulmonary surfactant protein A with dipalmitoylphosphatidylcholine and cholesterol at the air/water interface

Abstract: Interaction of pulmonary surfactant protein A (SP-A) with pure and binary mixed dipalmitoylphosphatidylcholine (DPPC) and cholesterol (3.5 wt%) at the air/saline, 1.5 m m CaCl 2 interface was investigated using a rhomboid surface balance at 37 Њ C. Surface tension-area isotherms were measured to access the surface active properties of the monolayers. The organization of DPPC and cholesterol in DPPC and DPPC/cholesterol mixed monolayers with or without SP-A at equilibrium surface tension ( Ϸ 23 mN/N) was reveal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
11
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(12 citation statements)
references
References 34 publications
1
11
0
Order By: Relevance
“…However, the amount of cholesterol in surfactant transferred from dispersions of BLES(chol) plus SP-A appears to be lower than in surfactant derived from BLES(chol), suggesting that SP-A could restrain the adsorption of cholesterol. Previously we have shown that SP-A interacts with the hydrophilic head groups of DPPC in DPPC spread monolayers (18). Electron microscopic studies indicate that SP-A also interacts with the head groups of DPPC in bilayers (28,29).…”
Section: Transfer Of Surfactants From Dispersions Of Bles(chol) In the Presence Of Sp-a To Clean Surfacesmentioning
confidence: 90%
See 4 more Smart Citations
“…However, the amount of cholesterol in surfactant transferred from dispersions of BLES(chol) plus SP-A appears to be lower than in surfactant derived from BLES(chol), suggesting that SP-A could restrain the adsorption of cholesterol. Previously we have shown that SP-A interacts with the hydrophilic head groups of DPPC in DPPC spread monolayers (18). Electron microscopic studies indicate that SP-A also interacts with the head groups of DPPC in bilayers (28,29).…”
Section: Transfer Of Surfactants From Dispersions Of Bles(chol) In the Presence Of Sp-a To Clean Surfacesmentioning
confidence: 90%
“…Cholesterol exists as cholesterol-rich (DPPC-poor) and cholesterol-poor (DPPC-rich) domains in DPPC/cholesterol mixed monolayers formed by successive spreading of DPPC and cholesterol (18). Cholesterol also exists as cholesterolrich and cholesterol-poor domains in biological membranes (31).…”
Section: Transfer Of Surfactants From Dispersions Of Bles(chol) In the Presence Of Sp-a To Clean Surfacesmentioning
confidence: 99%
See 3 more Smart Citations